Transforming concrete with steel slag: exploring the pores’ dual effect for sustainable and high−performance urban construction - Muhammad Farooq Akhtar; Ahmad Faraz; Anwar Khitab (Discover Civil Engineering)
Abstract This study explores the role of steel slag, a byproduct of steel production, as a complete replacement for natural coarse aggregates in concrete. Unlike conventional aggregates, the porous nature of steel slag aggregates promotes enhanced interlocking with the cement-sand matrix, improving adhesion and bond strength. A detailed evaluation of the slag aggregates was conducted, revealing an impact value of 29.5%, a bulk density of 1550 kg/m3, a crushing value of 31.3%, and a flakiness index of 10.95%. Concrete samples were prepared using an M20 mix ratio (1:1.5:3), and their performance was benchmarked against conventional concrete. The steel slag concrete exhibited compressive strengths of 9, 13, and 22 MPa at 3, 7, and 28 days, respectively. The mix exhibited a low slump of 25 mm and a compacting factor of 0.83 suitable for mass concrete applications. This research highlights the previously unreported synergistic effects of steel slag's porous structure and enhanced bonding characteristics on concrete performance. This research provides insights into steel slag's potential as a sustainable alternative to natural aggregates and highlights areas requiring further investigation, such as cost-effectiveness and long-term environmental impact. The findings suggest that steel slag aggregates can contribute to reducing natural aggregate dependency and may enhance urban infrastructure resilience when applied under suitable conditions.